THE SIGNIFICANCE OF FINANCIAL PAYMENTS IN THE CONTEXT OF CONTEMPORARY INNOVATIVE DEVELOPMENT OF THE REGIONAL ECONOMY - Narmamatov Ikhtiyor Bakhtiyorovich; Farmonov Behzod Farhod o'g'li (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The article examines the country’s payment system, which is formed and regulated by state laws and banking rules. It is noted that it includes: It is noted that it includes: the basic principles of organizing and implementing settlements; monetary units; types of payment documents; methods of payment; sources of payments; order of payments; rights and obligations of banks and economic bodies to control settlements. The work reveals their significance in more detail and provides specific proposals for their improvement.